2023
DOI: 10.1186/s12958-022-01045-7
|View full text |Cite
|
Sign up to set email alerts
|

Additional evidence for the role of chromosomal imbalances and SOX8, ZNRF3 and HHAT gene variants in early human testis development

Abstract: Background Forty-six ,XY Differences/Disorders of Sex Development (DSD) are characterized by a broad phenotypic spectrum ranging from typical female to male with undervirilized external genitalia, or more rarely testicular regression with a typical male phenotype. Despite progress in the genetic diagnosis of DSD, most 46,XY DSD cases remain idiopathic. Methods To determine the genetic causes of 46,XY DSD, we studied 165 patients of Tunisian ancest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Correspondingly, RSPO1 has been reported to be highly expressed in the female ovaries of P. sinensis (Liang, Meng, et al, 2019b). This study, however, revealed a surprising female‐biased expression of PsZNRF3 , with significantly higher expression levels in ovaries than in testes, diverging from mammalian patterns yet aligning with findings in Neocaridina denticulate (Harris et al, 2018; Muncaster et al, 2023; Rjiba et al, 2023). Additionally, the study compared expression levels (FPKM values) of PsZNRF3 across different embryonic development stages between females and males, revealing consistently higher expression in females.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Correspondingly, RSPO1 has been reported to be highly expressed in the female ovaries of P. sinensis (Liang, Meng, et al, 2019b). This study, however, revealed a surprising female‐biased expression of PsZNRF3 , with significantly higher expression levels in ovaries than in testes, diverging from mammalian patterns yet aligning with findings in Neocaridina denticulate (Harris et al, 2018; Muncaster et al, 2023; Rjiba et al, 2023). Additionally, the study compared expression levels (FPKM values) of PsZNRF3 across different embryonic development stages between females and males, revealing consistently higher expression in females.…”
Section: Discussionsupporting
confidence: 81%
“…These sex‐specific loci were annotated, revealing that 19 SNPs were situated within the Zinc and ring finger 3 ( ZNRF3 ) gene, known for its role in testis determination in mammals and which has been the focus of significant research in recent years (Rjiba et al, 2023). Mammalian sex determination is governed by the antagonistic interplay between the testis‐determining (SRY‐SOX9‐FGF9) pathway and the ovary‐promoting (RSPO1‐WNT/β‐catenin‐FOXL2) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function variants of FLNA have been causally associated with neurodevelopmental and skeletal disorders ( 15 , 16 ). Although 46,XY DSD is not a common symptom of patients with FLNA mutations, hypospadias and cryptorchidism have been reported in a few cases ( 7 , 8 , 17 ). Importantly, Carrera-Garcia et al .…”
Section: Discussionmentioning
confidence: 99%
“…FLNA is known as a causative gene for neurodevelopmental and skeletal abnormalities ( 6 ). Rare variants in FLNA have been identified in a few patients with 46,XY DSD without neuronal or skeletal anomalies ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%